2020
DOI: 10.15414/afz.2020.23.03.155-160
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth-production parameters of Lolium perenne L. turf after application of concentrated polysulfide fertilizer

Abstract: The changes in growth rate, daily production of above-ground phytomass and lawn density of turfgrass after application of fertilizer based on polysulfide (Sulka NKS+) were evaluated in Nitra (the Slovak Republic) climatic conditions. The polysulfide preparation was applied 2-times, 4-times and 6-times during the vegetation period in 2015–2017 and the effect was compared with a zero control. Stimulatory effect of Sulka NKS+ was shown in the average daily gain of grass height and average daily gain of abovegroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…To sum up, we have demonstrated that the accumulation of the aboveground biomass (according to dry weight) was the highest in V8 (finely ground apatite in combination with BI14 and BS89 strains), whereas that of the total biomass was maximal in V5, where it was 17% higher than in the control. Ryegrass, similar to other crops, needs enough nutrients for growing without decreasing its regenerative capacity, density, and productivity [23]. As a rule, most mineral fertilizers are obtained in granular form.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, we have demonstrated that the accumulation of the aboveground biomass (according to dry weight) was the highest in V8 (finely ground apatite in combination with BI14 and BS89 strains), whereas that of the total biomass was maximal in V5, where it was 17% higher than in the control. Ryegrass, similar to other crops, needs enough nutrients for growing without decreasing its regenerative capacity, density, and productivity [23]. As a rule, most mineral fertilizers are obtained in granular form.…”
Section: Discussionmentioning
confidence: 99%